Voice of history - The British Library Publication (Yokshire : The British Library Publication, 2004)
Excerpts from speeches by various leaders of the 20th century
Contents on sound disk: To Edison From Colonel Gouraud, Introducing Mr Gladstone - The Phonographer's Salutation (3:09) - Speech on budget(3:27) - Speech on budget(3:47) - Labour (3:31) -In Memory Of Comrade Yakov Mikhailovich, Chairman Of The All Russia Central Executive Commitee (1:20) -Saint Patrick's Day address (2:49) - Labour Party 1929 Election. Part 1 Unemployment (4:47) - Address by the prime minister at the Empire Rally of Youth (3:15) - Speech to the Mexican people (3:37) -The prime minister's speech at Heston Airport on his return from Munich Sept. 30th, 1938 (2:42) - This was their hour (5:03) -Radio broadcast to the Soviet people (2:35) - Address to the Congress of the US (6:19) -Speech at the opening assembly of the United Nations (2:59) -Suffragette (3:18) -Politics and the home (5:19) -The woman's opportunity (4:29) -The new outlook for women (4:22) -Nancy Astor lays foundation stone (2:07) - women against the war (2:26) - Women demand equal compensation (0:21) -Women demand equal compensation (0:37) -Close - up Edith Summerskill (1:16) -The Gospel of wealth (5:53) -Land and labour (4:16) -The future of British industry (3:43) -The return to prosperity and how the League [of nations] is helping (2:52) - A message to the empire (3:04) - Abdication speech (6:59) - A broadcast message to children (3:20) - A message broadcast on D - Day 6th June 1994 (4:15) - Speech on education (1:41 ) -The Jewish homeland (3:10) -The relevance of Chiristianity (2:04)-His spiritual message to the world (6:04) - My message to the world of Islam (6:43) - In aid of the Light Brigade Relief Fund (2:31) -Don't forget (2:34) -Address to boy scouts (3:36) -The social and humanitarian work of the League of Nation (3:29 )-Toc H festival speech (1:51) -Speech at European Congress on Nuclear Disarmament (7:79)
Keywords: Speeches, addresses, etc